A Comprehensive Analysis of Eco‐Friendly Cs2SnI6 Based Tin Halide Perovskite Solar Cell through Device Modeling. Issue 3 (26th January 2023) - Pal, Debashish
Abstract: The choice of appropriate materials is of paramount importance in realizing a high efficiency perovskite solar cell. Lead free eco‐friendly perovskite solar cell architecture is theoretically investigated using solar cell capacitance simulator (SCAPS) for device performance. Preliminary investigations on Cs2 SnI6 solar cell architectures have indicated that the presence of hole transport layer is crucial in achieving an open‐circuit voltage greater than 0.6 V. The presence of a valence band offset between the Cs2 SnI6 absorber and hole transport layer has a significant detrimental impact on the short‐circuit current density and fill factor of the cell. A novel device architecture employing TiO2 as an electron transport material and Cu2 O as a hole transport material is proposed to overcome the limitations associated with the current designs. Theoretical investigations are carried out employing 1D SCAPS simulation program in order to optimize the structure by varying the perovskite thickness, bandgap, and defect concentration. The proposed solar cell after optimization has a practically realizable power conversion efficiency of 17.77%. Abstract : The proposed nontoxic, lead free, all‐inorganic Cs2 SnI6 perovskite solar cell has the potential to achieve a power conversion efficiency of over 17% with TiO2 as electron transport layer, Cu2 O as hole transport layer along with Au/Ni back contact with promising open‐circuit voltage, short‐circuit current, fill factor, and an excellent spectral response.2